PENDAMPINGAN MENINGKATKAN KESADARAN DAN PERILAKU BAIK DALAM MENGGUNAKAN GADGET PADA ANAK NELAYAN MELALUI VIDEO EDUKATIF - Hidayah, Linta Wafdan; Mulyadi, Mulyadi; Tamam, Badrut (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2025)
Not only adults, but also school-age children are often greatly impacted by the rapid developments in this technological era. Smartphones, or what we better know as gadgets, seem to be a mandatory item that parents must provide for their children so they don't miss out on fast information. The use of gadgets does have many positive impacts for school-age children, for example increasing knowledge and experience that they have never had before, but sometimes the negative impacts outweigh the positive ones. In fact, many experience negative impacts and addiction. The impact of gadget addiction greatly affects the emotions and behavior of children who are addicted to gadgets. Therefore, the author and the community service team provided education to fishermen's children about the dangers of gadgets through educational videos. In this case, the community service team used two videos in the community service implementation. The first video from Pondok Kreativ entitled "Gadget Addiction" and the second video from Healthy Kids entitled "When Lala Plays Gadgets". This community service was carried out at Pagagan Elementary School, Pademawu District, where the majority of students are fishermen's children. Fishermen's children sometimes lack extra attention from their parents who are busy earning a living as fishermen. Day and night, their parents are at sea, and in the morning, they go to the market to sell their catch. This community service activity has made 90% of Pagagan Elementary School students aware of the benefits of educational videos, and they have even pledged to reduce their daily use of gadgets by engaging in positive activities like studying, helping their parents, and playing with friends.